Macrochelid mite (Acari: Gamasida) associated with dung beetles in Baluran National Pak, East Java, Indonesia - Sri Hartini; Dhian Dwibadra; Masahiro Ohara; Gen Takaku (Treubia, 2015)
Eight mite species of the family Macrochelidae (Acari: Gamasida) were collected from the body surface of dung beetles in Baluran National Park, East Java, Indonesia. Of these, one species, Macrocheles subwallacei sp. nov., was describe as new to science. Female of Macrocheles crispa (Berlese, 1910) was rediscribed and the male was described for the first time. The remaining six species were Neopodocinum Â jaspersi (Oudemans, 1900), M. dispar (Berlese, 1910), M. hallidayi Walter & Krantz, 1986, M. entetiensis Hartini & Takaku, 2005, M. jabarensis Hartini & Takaku, 2003 and M. persimilis Hartini, Dwibadra & Takaku, 2007.